IMPLEMENTATION OF THE SEVEN TOOLS METHOD FOR PRODUCT QUALITY CONTROL: A CASE STUDY AT RUMAH TEMPE INDONESIA - Samuel Christian Ananda; Muhammad Traya Alfarizi; Ruth Angelica Sitorus; Ghina Khalisah; Muhammad Ikhsan Mubaraq; Fany Apriliani (Syarif Hidayatullah State Islamic University Jakarta, 2025)
This study applied the Seven Quality Control Tools to Soyagreen tempe products produced at Rumah Tempe Indonesia from 14 to 19 April, 2025. Analysis via Check Sheets, Flowcharts, Histograms, Pareto Diagrams, Control Charts, Scatter Plots, and Fishbone Diagrams revealed a 12.19% defect rate out of a total production of 1,091 units, consisting of 96% under-fermentation and 4% spoilage. Regression analysis found that each 1 °C increase in fermentation temperature led to an average of 7.57 additional defects. To address these findings, we recommend implementing a preventive-maintenance schedule daily calibration and cleaning of sensors, weekly deep-cleans of fermenter piping and external surface, monthly replacement of gaskets and seals, and quarterly servicing of heating and humidification components. This should be complemented by automated temperature-humidity controls, standardized standard operating procedures (SOP), operator training, and regular Seven Tools audits.